Hubungan antara lingkar pinggang dengan kadar hematokrit pada pria dewasa muda - Villarsi, Devinda; Rotty, Linda W.A.; Pandelaki, Karel; Wantania, Frans E. (e-CliniC, 2016)
Abstract: Central obesity plays an important role in the changes of blood circulation that can lead into several chronic diseases. The changes of blood circulation can be detected as earlier as possible by checking the hematocrit levels regularly. This study was aimed to determine the correlation between waist circumference and hematocrit levels in young adult males, This was a descriptive analytical study with a cross sectional design. Respondents were young adult males aged 20-28 years. This study was conducted from October 13 until November 11, 2016. Respondents were 38 young adult males consisting of 27 males with central obesity and 11 males without central obesity. The result of Spearman’s rho analysis of the correlation between waist circumference and hematocrit level resulted in r=0.156 and p=0.350. Conclusion: There was a weak positive correlation between waist circumference and hematocrit levels in young adult males but was not statistically significant.Keywords: central obesity, hematocrit, young adult men. Abstrak: Obesitas sentral berperan penting terhadap terjadinya perubahan aliran darah dalam tubuh manusia yang selanjutnya dapat menimbulkan beberapa penyakit kronik. Perubahan aliran darah dapat dideteksi sedini mungkin dengan melakukan pemeriksaan kadar hematokrit secara teratur. Penelitian ini bertujuan untuk mengetahui hubungan antara lingkar pinggang dengan kadar hematokrit pada laki-laki dewasa muda. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Responden penelitian ialah mahasiswa laki-laki berusia 20-28 tahun. Penelitian ini berlangsung dari tanggal 13 Oktober - 11 November 2016 dengan responden berjumlah 38 orang yang terdiri dari 27 mahasiwa obes sentral dan 11 mahasiswa non-obes sental. Hasil analisis uji Spearman’s rho antara lingkar pinggang dengan kadar hemoglobin dari 38 responden diperoleh koefisien korelasi r = 0,134 dengan nilai p = 0,422. Simpulan: Terdapat hubungan positif lemah yang tidak bermakna antara lingkar perut dan hemoglobin. Kata kunci: obesitas sentral, hematokrit, pria dewasa muda